LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK SELF-MANAGEMENT UNTUK MENGATASI PROKRASTINASI AKADEMIK SISWA MTSN 3 PURWAKARTA DI MASA PANDEMI COVID-19 - Eri Abduloh; Siti Fatimah; Tita Rosita (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
Academic procrastination is a problem that often occurs among SMP/MTs students. The purpose of this study was to determine the description of guidance services with self-management techniques to overcome academic procrastination of students at MTsN 3 Purwakarta during the covid-19 pandemic. This research uses descriptive qualitative method. The population in the study was 32 students in class VIII E MTsN 3 Purwakarta. Based on the results of interviews with BK teachers and homeroom teachers from the population, there were 6 students who experienced academic procrastination. Collecting data in this study are interviews, observation and documentation. From the results of the data analysis, group guidance services have been provided with self-management techniques through several stages and are going well. From these stages, it produces an overview of group guidance services with self-management techniques that can overcome academic procrastination of students at MTsN 3 Purwakarta during the covid-19 pandemic. Keywords:   Group Guidance, Self-Management Techniques, Academic Procrastination